2017
DOI: 10.5194/amt-10-1139-2017
|View full text |Cite
|
Sign up to set email alerts
|

Collection efficiency of <i>α</i>-pinene secondary organic aerosol particles explored via light-scattering single-particle aerosol mass spectrometry

Abstract: Abstract. We investigated the collection efficiency and effective ionization efficiency for secondary organic aerosol (SOA) particles made from α-pinene + O 3 using the singleparticle capabilities of the aerosol mass spectrometer (AMS). The mean count-based collection efficiency (CE p ) for SOA across these experiments is 0.30 (±0.04 SD), ranging from 0.25 to 0.40. The mean mass-based collection efficiency (CE m ) is 0.49 (±0.07 SD). This sub-unit collection efficiency and delayed vaporization is attributable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Differences in the spectra of prompt and delayed particles were also recently reported for ammonium sulfate and laboratory-generated secondary organic aerosols (SOAs), both with a substantial fraction of delayed particles (Robinson et al, 2017). Indeed, the pattern of sulfate ions between prompt and delayed particles in their study is similar to what is shown in Fig.…”
Section: Mass Spectral Differences Between Prompt and Delayed Particlessupporting
confidence: 72%
See 4 more Smart Citations
“…Differences in the spectra of prompt and delayed particles were also recently reported for ammonium sulfate and laboratory-generated secondary organic aerosols (SOAs), both with a substantial fraction of delayed particles (Robinson et al, 2017). Indeed, the pattern of sulfate ions between prompt and delayed particles in their study is similar to what is shown in Fig.…”
Section: Mass Spectral Differences Between Prompt and Delayed Particlessupporting
confidence: 72%
“…The broadening of the traditional AMS mass distribution to larger sizes due to delayed particles was also observed during the Mexico City and Bakersfield field studies (Cross et al, 2009;Liu et al, 2013) and the alpha-pinene SOA laboratory study (Robinson et al, 2017). Thus, d va-LS instead of d va-MS is a more reliable parameter to represent particle size in the AMS.…”
Section: Relevance Of Lssp Results To Standard Ams Measurements 331mentioning
confidence: 91%
See 3 more Smart Citations